Analysis of Blended Learning Design to Enhance Elementary Students' Creativity and Motivation - Purnomo, Edy; Waris, Waris; Adhim, Fauzan (Newinera Publisher, 2025)
In this research, it was critical to implement a blended learning model with the aim of improving creativity and learning motivation of the elementary students of Pasirian 01 Public Elementary School, Pasirian Subdistrict, Lumajang Regency. The study used a descriptive qualitative case study design to discuss the involved process and experiences, difficulties and adaptive techniques in the amalgamation of resource-limited face-to-face and web-based education in a rural setting. Direct observations, in-depth interviews of the teachers, students and the principal, and review of supporting data such as student portfolios, lesson plans as well as communication records were used to collect the data. These results indicate that the blended learning model, based on the low-bandwidth digital tools, flexibility in scheduling, and creatively based on project-based assignments, has an important contribution to making students engaged, expressing themselves, and self-motivated. Teachers also transformed their role towards facilitating student-centered learning where learners were also more confident and excited to work, especially on assignments that requiring creativity and accentuating autonomy. Nevertheless, the study also emphasizes such difficulties as unequal access to devices and connectivity, deficiencies of digital literacy among teachers and parents, and the increased workload due to the preparation of dual-modality instruction. Responsive approaches implemented by the school, inter alia, by increasing personal meetings and strengthening partnerships between schools and home as well as improving capacity development of teachers via peer-led workshops, loaning technologies, and reinforcing links between students and parents helped address them.